Homeschooling, Perceived Social Isolation, and Life Trajectories: An Analysis of Formerly Homeschooled Adults. Issue 2 (3rd April 2022) - Hamlin, Daniel; Cheng, Albert
ABSTRACT: A longstanding critique of homeschooling is that it isolates children from mainstream society, depriving them of social experiences needed to thrive as adults. Although a small number of empirical studies challenge this criticism, this research tends to be derived from self-reports of homeschooling parents about their children. In this study, analyses of qualitative interviews (n = 31) and survey data (n = 140) of adults who were homeschooled as children are performed. Most interview participants described conventional and unconventional social experiences that they felt had satisfied their social needs while being homeschooled. Participants who were homeschooled for all or most of their K-12 education had less exposure to mainstream school-based social opportunities but reflected that homeschooling had not hindered their ability to navigate society effectively. Analyses of survey data seemed to echo this finding. Across four social and life outcomes (i.e. college attendance, household income, marital status, and subjective wellbeing), no statistical differences were observed between short-term homeschoolers (1–2 years) who spent nearly all of their K-12 education in brick-and-mortar schools and long-term (10–12 years) and substantial (3–9 years) homeschoolers who had less exposure to mainstream social opportunities available in brick-and mortar schools. This study advances the literature by drawing on qualitative and quantitative data from formerly homeschooled adults and by differentiating homeschoolers based on how many years they were homeschooled.